The BLOCKHAIN UNTUK TRANSPARANSI DAN EFISIENSI DISTRIBUSI ZAKAT DALAM PERSPEKTIF HUKUM ISLAM - Jinoto, Devin (LPPM STAI Muhammadiyah Probolinggo, 2025)
Enhancing transparency and efficiency in zakat management is an urgent necessity, considering challenges such as non-transparent reporting, regulatory uncertainty, and societal resistance. This study aims to explore the application of blockchain technology as a solution to these challenges. The main questions addressed in this research are how blockchain technology can improve the transparency, accountability, and efficiency of zakat distribution and the extent to which this technology aligns with Islamic legal principles. The research methodology employs a normative juridical approach by analyzing relevant zakat regulations. Data were collected through literature studies. The results show that blockchain features such as decentralization, immutability, and audit trails can significantly enhance accountability and trust in zakat institutions. However, technical challenges such as inadequate infrastructure and training needs, as well as insufficient regulatory support, remain major obstacles. These findings provide important contributions to understanding how blockchain can be adapted to support sharia-compliant zakat management. In conclusion, the adoption of blockchain has the potential to revolutionize zakat management systems with better transparency and efficiency, but it requires regulatory support, training, and global collaboration. Future research is recommended to focus on developing technical standards and evaluating implementation in various local and international contexts. Keywords: Blockchain, Zakat, Islamic Law.